2022
DOI: 10.7759/cureus.30314
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy Interventions for Preventing Spinal Curve Progression in Adolescent Idiopathic Scoliosis: A Systematic Review

Abstract: Adolescent idiopathic scoliosis (AIS) is an abnormal curvature of the spine that appears in late childhood or adolescence. The aim of this systematic review was to present and synthesize the most relevant therapeutic advice and evidence on the efficacy of physiotherapy exercises for preventing the growth of spinal curvature caused by adolescent idiopathic scoliosis. "Adolescent idiopathic scoliosis," "exercise," "Cobb angle," and "physiotherapy" were the sole keywords used for the published research. Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Exercises for mild scoliosis are the first line of treatment that significantly impacts strength, spinal mobility, balance, and pain for people with scoliosis. 27 In this study, there are several research limitations. First, the number of samples was small.…”
Section: Discussionmentioning
confidence: 94%
“…Exercises for mild scoliosis are the first line of treatment that significantly impacts strength, spinal mobility, balance, and pain for people with scoliosis. 27 In this study, there are several research limitations. First, the number of samples was small.…”
Section: Discussionmentioning
confidence: 94%
“…The efficacy of bracing increases with more time spent in the brace, so compliance is the key to treatment for both patients and parents [13,80,81]. It is also suggested to combine the brace with specific physiotherapy exercises for scoliosis (PSE) according to the SOSORT guidelines [24,82,83].The articles in the available scientific literature about the number of hours/day of bracing showed that the more hours per day the brace is worn, the better the result [30,83]. For this reason, braces are usually prescribed for at least 18 h/day, and they are usually removed for showers, swimming, physical education, and sports [84].…”
Section: Discussionmentioning
confidence: 99%
“…25 Recent comprehensive systematic reviews also examined compliance of orthotic treatment, 26 predictive factors of orthotic treatment outcomes [27][28][29] and comparison between orthotic treatments and other treatments, including physiotherapy, exercise intervention and surgical treatment. [30][31][32][33][34][35][36] Our initial and informal review of systematic reviews of studies that have investigated orthotic treatment in AIS revealed some overlap across studies; however, the standalone studies and the systematic reviews of those studies may not yield overarching essential insights into the use, mechanisms, effectiveness and long-term outcomes of orthotic treatment in AIS. Moreover, they may not yield new and important information.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…However, most of those systematic reviews focused on different orthotic designs and the effectiveness of orthotic treatment,16ā€“24 and only one systematic review evaluated the effectiveness of different bracing concepts in AIS 25. Recent comprehensive systematic reviews also examined compliance of orthotic treatment,26 predictive factors of orthotic treatment outcomes27ā€“29 and comparison between orthotic treatments and other treatments, including physiotherapy, exercise intervention and surgical treatment 30ā€“36…”
Section: Introductionmentioning
confidence: 99%